The role of cis-zeatin-type cytokinins in plant growth regulation and mediating responses to environmental interactions - Schäfer, Martin; Brütting, Christoph; Meza-Canales, Ivan David; Großkinsky, Dominik K; Vankova, Radomira; Baldwin, Ian T; Meldau, Stefan (Journal of experimental botany, 2015)
Cytokinins (CKs) are well-established as important phytohormonal regulators of plant growth and development. An increasing number of studies have also revealed the function of these hormones in plant responses to biotic and abiotic stresses. While the function of certain CK classes, including trans-zeatin and isopentenyladenine-type CKs, have been studied in detail, the role of cis-zeatin-type CKs (cZs) in plant development and in mediating environmental interactions is less well defined. Here we provide a comprehensive summary of the current knowledge about abundance, metabolism and activities of cZs in plants. We outline the history of their analysis and the metabolic routes comprising cZ biosynthesis and degradation. Further we provide an overview of changes in the pools of cZs during plant development and environmental interactions. We summarize studies that investigate the role of cZs in regulating plant development and defence responses to pathogen and herbivore attack and highlight their potential role as 'novel' stress-response markers. Since the functional roles of cZs remain largely based on correlative data and genetic manipulations of their biosynthesis, inactivation and degradation are few, we suggest experimental approaches using transgenic plants altered in cZ levels to further uncover their roles in plant growth and environmental interactions and their potential for crop improvement.
Keywords: prenylated tRNA.; Food Chain; herbivory; Herbivory; pathogen; Abiotic stress; fyziologie rostlin; plant growth; Plant Development; Gene Expression Regulation, Plant; regulace genové exprese u rostlin; Plant Physiological Phenomena; cis-zeatin; zeatin; c-io6A37-tRNA; býložravci; regulátory růstu rostlin; potravní řetězec; vývoj rostlin; Zeatin; Plant Growth Regulators